Are the States Sovereign? - Timothy Zick (Washington University Law Quarterly, 2005)
This Article is the first effort to bridge the scholarly divide by means of a conceptual comparison of state sovereignty here and abroad. To be clear, this Article does not claim that the substance of state sovereignty is the same in all respects for states as it is for nations. The states and nation-states are obviously vastly different creatures, with vastly different powers and rights. However, their claims to sovereignty, the manner in which these claims are made, and the implications of states’ success in making such claims, are indeed similar and thus worth comparing. This Article will draw upon certain insights of international scholars in addressing whether the American states are “sovereign,” and if so in what sense. Based upon an examination of the evolution of the concept of sovereignty, this Article concludes that the states are indeed meaningfully sovereign.
Keywords: Sovereignty (Political science); International; United States